Talent development: linking the stakeholders to the process - Pankhurst, A.; Collins, D.; Macnamara, A. (Journal of Sports Sciences, 2013)
The three stakeholders (coaches, parents and the National Governing Body) in Talent Identification and Development (TID) are important factors in athlete development. How each of them perceive the key constructs of Talent Identification and Development (i.e. sport specialisation and selection, practice, athlete development, junior and adult success, and the role of the stakeholders), and the coherence of that understanding is not well understood. This study focuses on junior performance tennis and investigates the perceptions of coaches, parents and sports organisations (a National Governing Body) of the five key constructs of Talent Identification and Development. We were interested in examining (a) the extent to which stakeholder perceptions relate to research, (b) the coherence of each stakeholder's perceptions and (c) the extent to which there is coherence between what stakeholders understand each other thinks. Seventy-five coaches, parents, and National Governing Body staff completed a questionnaire that asked participants to rate their degree of agreement/disagreement with researched `principles' of Talent Identification and Development. The results suggest that stakeholders do not strongly agree with the research supporting principles of Talent Identification and Development. Furthermore, a significant lack of coherence of stakeholder perceptions was evident. This lack of coherence was also evident in each group's understanding of what the other stakeholders believed. The impact of these results on the Talent Identification and Development process is discussed.